Anything, anywhere, anytime? Developing measurement instruments to assess the spatial and temporal fragmentation of activities - Alexander, B; Hubers, C; Schwanen, T; Dijst, M; Ettema, D (Pion, 2011)
Developments in transportation and information and communication technologies (ICTs) have facilitated the process labeled activity fragmentation. In this process, the weakened associations between activity, time and place that ICTs made possible facilitate the disintegration of activities into smaller subtasks, which can then be performed at different times and at different locations. However, until now discussion of the fragmentation of activity hypothesis has been limited to the theoretical domain and largely absent from the empirical domain. In the study reported here we connect both domains by (1) developing a set of measures of activity fragmentation and (2) applying them to study the fragmentation of the activity of paid work using combined activity, travel and communication diary data collected in the Netherlands in 2007 in order to assess the performance of these indicators. The results show that the indicators differentiate between the multiple facets of activity fragmentation (such as the number, dispersion and configuration of fragments). The preliminary analyses also suggest that, although the temporal fragmentation of activities appears to be or to have become more common, spatial activity fragmentation is rather limited.